PENANGANAN PENYELESAIAN PERKARA PERDATA PERBUATAN MELAWAN HUKUM REGESTER PERKARA NOMOR 13/PDT.G/2019/PN Kdr (Study Kasus Di Pengadilan Negeri Kediri) - Hidayah, Fajar Khoirul; Nurbaedah, Nurbaedah (Universitas Islam Kadiri, 2023)
The purpose of the research in the settlement of civil cases is the study of cases of unlawful acts, case registration number 13/Pdt.G/2019/PN Kdr/2019 at the Kediri District Court to study and find out the construction of civil law in the trial process of civil judges in the event of the commencement of unlawful acts. using the birth certificate Number 126/IND/1971 in the name of Endang Murtiningrum as the basis for requesting a Declaration of Inheritance to replace the form of SHM Number 31/Desa Singonegaran on behalf of Toeminah bint Sastrorejo, the wife of Moersad who did not have biological children during her lifetime. Through the method of inheritance, researchers analyzed using empirical methods based on legal identification in civil case court decisions at the Kediri District Court Number 13/Pdt.G/2019/PN Kdr jucto Decision of the Surabaya High Court regester Number 604/PDT/2019/PT.SBY jucto Decision Cassation Supreme Court of the Republic of Indonesia esia Regester Number 2800 K/Pdt/2020 jucto decision of the Supreme Court of the Republic of Indonesia Number 251 PK/Pdt/2022 which is the basis for consideration of judicial judges in examining, considering and deciding (object of dispute) in civil lawsuits which are null and void. the name of Endang Murtiningrum, Declaration of inheritance and SHM No. 2139/Kelurahan in the name of Endang Murtingrum by returning to the origin of SHM No. 31/Desa Singonegaran on behalf of Toeminah bint Sastrorejo who died in 1994 in Singonegaran Village, Pesantren District, Kediri City.